2014
DOI: 10.1111/1468-4446.12080
|View full text |Cite
|
Sign up to set email alerts
|

Social media in the 2011 Egyptian uprising

Abstract: This paper uses Gallup poll data to assess two narratives that have crystallized around the 2011 Egyptian uprising: (1) New electronic communications media constituted an important and independent cause of the protests in so far as they enhanced the capacity of demonstrators to extend protest networks, express outrage, organize events, and warn comrades of real-time threats. (2) Net of other factors, new electronic communications media played a relatively minor role in the uprising because they are low-cost, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 49 publications
(52 reference statements)
1
49
0
3
Order By: Relevance
“…SNS afford users multimedia rich, interactive platforms to develop and manage their online social spheres, and facilitate the sharing of extensive amounts of personal and social information. These platforms are used for a range of purposes from developing and managing personal social networks, to promoting business enterprise and organizing mass social movements (Brym et al ; Vitak ). As global users have grown to number in their billions (Ofcom ; Statista ), use of SNS has been most often associated with young adults (Ofcom ; Pew Research ) although use is reported throughout the life‐course including among the over 50s (Khalaila and Vitman‐Schorr ; Yu, McCammon, Ellison and Langa ).…”
Section: Introductionmentioning
confidence: 99%
“…SNS afford users multimedia rich, interactive platforms to develop and manage their online social spheres, and facilitate the sharing of extensive amounts of personal and social information. These platforms are used for a range of purposes from developing and managing personal social networks, to promoting business enterprise and organizing mass social movements (Brym et al ; Vitak ). As global users have grown to number in their billions (Ofcom ; Statista ), use of SNS has been most often associated with young adults (Ofcom ; Pew Research ) although use is reported throughout the life‐course including among the over 50s (Khalaila and Vitman‐Schorr ; Yu, McCammon, Ellison and Langa ).…”
Section: Introductionmentioning
confidence: 99%
“…We now know that the prominence of young people in the protests owed more to the demography of the countries than the over-representation of the young, and that all age groups were present and all their voices could be heard amid the protests in Tunis and Cairo [1,2]. Surveys have not produced evidence of change over time or differences by age in political orientations that a new political generation would create [3,4].…”
Section: Some Knownsmentioning
confidence: 99%
“…The daily number of tweets originating in Egypt with the "#egypt" hashtag was roughly 18,000 between January 25 (the day the uprising began) and February 28 [9]. One user in Cairo generated 60,000 words alone during the 18-day revolution, a total of 1,500 tweets [10].…”
Section: Twitter In Egyptmentioning
confidence: 99%
“…How can even sincere democratic representatives respond correctly to public opinion when empirical evidence of it appears to be so malleable, so vulnerable to framing effects? [24] People are more likely to turn to trusted sources such as familiar political figures or they seek for fitting arguments or perspectives within media frames [9]. If complex issues must be explained to the audiences, the media and opinion leaders are bound to play an important role.…”
Section: Framing Theorymentioning
confidence: 99%